Protocol for an outcome assessor-blinded pilot randomised controlled trial of an ion-exchange water softener for the prevention of atopic eczema in neonates, with an embedded mechanistic study: the Softened Water for Eczema Prevention (SOFTER) trial - Joanne R Chalmers; Sanja Kezic; Zarif K Jabbar-Lopez; Nikeeta Gurung; Danielle Greenblatt; Annette Briley; Kim Suzanne Thomas; Tony Frost; John E A Common; Heidi H Kong; Julie A Segre; Simon Danby; et al. (BMJ Open)
Introduction Atopic eczema affects 20% of UK children, and environmental factors are important in its aetiology. Several observational studies suggest an increased risk of atopic eczema in children living in hard water areas. The Softened Water for Eczema Prevention pilot trial tests the feasibility of installing domestic ion-exchange water softeners around the time of birth to reduce the risk of atopic eczema in children with a family history of atopy. A further aim is to explore the pathophysiological mechanisms for this in an embedded mechanistic study.Methods and analysis Multicentre parallel group assessor-blinded randomised controlled pilot trial. Participants are newborn babies (n=80) living in a hard water (>250 mg/L calcium carbonate) area at risk of developing atopic eczema because of a family history of atopy. Participants will be randomised prior to birth in a 1:1 ratio. The intervention group will have an ion-exchange water softener installed prior to birth. The control group will receive their usual domestic hard water supply. Follow-up will be until 6 months of age. Data will be collected at birth (baseline), 1, 3 and 6 months of age. The main outcome is the proportion of eligible families screened who are willing and able to be randomised. Several secondary feasibility and clinical endpoints will also be evaluated, alongside mechanistic outcomes. Data will be analysed on an intention-to-treat basis. There will be no hypothesis testing for the clinical outcomes. Study acceptability will be evaluated through semistructured interviews.Ethics and dissemination This study has been reviewed and given a favourable opinion by the North West–Liverpool East Research Ethics Committee (Ref: 17/NW/0661). The results of the study will be reported at international conferences and in peer-reviewed scientific journals. We will send participating families a summary of the pilot trial results.Trial registration number NCT03270566.